Getting into host’s skin: initial immune response to Schistosoma mansoni infection - Orrico-Ferreira, Carolina Melo; Cruz, Paulo Emilio Oliveira; Rios, Joao Vitor Borges; da Silva Rosa, Wellington; Santos, Beatriz de Souza; Silva, Raphael Chagas; Pinheiro, Carina Silva; Figueiredo, Barbara Castro-Pimentel (Frontiers in Immunology, 2025)
Schistosoma mansoni initiates infection through active skin penetration by cercariae, triggering early immune responses that are crucial to disease establishment. In naïve hosts, parasite antigens elicit an initial Th1-type response that is rapidly modulated to a Th2 profile by parasite-derived immunomodulatory molecules, including proteases and eicosanoids. Upon reinfection, prior sensitization enhances Th2 responses, IgE production, and eosinophil recruitment, while promoting regulatory mechanisms that limit pathology and favor chronic infection. Key molecules such as cercarial elastase (SmCE) interfere with antigen presentation and antibody function, facilitating immune evasion. This review explores the early immune responses elicited at the cutaneous interface during primary S. mansoni infection and reinfection, emphasizing the dynamic interplay between host defense mechanisms and parasite-driven immunoregulation. Understanding these early skin-stage events reveals how S. mansoni balances immune activation and suppression, offering valuable targets for vaccine development and immune-based interventions.